PRONUNCIATION OF ENGLISH HOMOPHONES: A STUDY OF UNDERGRADUATE EFL STUDENTS - Annida, Tia; Hardiah, Mei; Maisarah, Ira (UNIB Press, 2025)
The aims of this study are to find out students’ knowledge and pronunciation about homophone by students of eighth semester of English education study program at Bengkulu University. It employs qualitative research methods to collect data, including knowledge test and pronunciation test by using Praat and Live transcribe application. The result of this research revealed that in the knowledge test there are 36.5% students are in the excellent category and 32% students in the good category. Furthermore, 14.9% in the enough category, 16.2% students in the category of poor and 1.4% students in the category of very poor. While, in the pronunciation test there are 2 students in the good pronunciation, 2 students in the close to good pronunciation, and 6 students in the not good pronunciation. Moreover, there were 2 vowel, 2 consonant, and 3 diphthongs that the most students’ difficulty in pronouncing homophone, the phoneme are vowel /ɔ/, and /u/; consonant /t/, /d/, diphthong /ʊɚ/, /əʊ/ and /eɪ/. Based on the findings, the researcher found that students of eighth semester of English education study program still not good enough in mastering homophone.